O conselho do Artigas: um estudo sobre o estado autocrático - Sousa, Ana Maria da Silva Gomes de Oliveira Lucio de (2006)
Starting from the practice carried out by a Conselho de escola , between 1985 and 2000, this work analyzed the authoritarianism of the formal democracy that is expressed in the relations between the State and the social demands, as the shape of criminalization. The pedagogical political project developed by this Conselho de Escola is situated in the context of the implementation of the proposals of democratic management in the public net of education of the State of São Paulo. This project was fortified in the period between 1995 and 1998 with the implementation of the first measures that take part of the reform of the State s Public Education Net, still in course. Such measures, of neoliberal stamp, were applied according to the educational changes for the Brazilian public sector under the orientation of the Decenal Plan of Education For Everybody, made official in 1993, delimited by the Conferência Mundial de Educação para todos carried out in 1990. The neoliberal projects expressed the objective of the reformulation of the role of the State in the economy, with the financial and commercial opening, to the process of desregulamentation of the legislation of the labor law and the contention of the expense in the publics. The neoliberal model started in Brazil, although the trial had started before, in the government of Fernando Collor de Mello in 1989, getting deeper in Fernando Henrique Cardoso s govern in 1994, being consolidated in the government of Luis Inácio Lula da Silva, after 2003. In the State of São Paulo, the neoliberal measures in the educational field were implemented during the govern of Mário Covas, from 1995 to 1998, and triggered off in the deepening of questions that contribute for the shrinkage of conquests that end up straightly in the access and in the quality of the public education and bring a huge impact in the action of the APEOESP. The intervention inside the school studied is characterized by the increase of the repression process realized by the State, during the 2000s